Sex as a Potential Moderator for Baclofen Response in the Treatment of Alcohol Dependence - Kirsten C. Morley; Kirsten C. Morley; Eva Louie; Tristan Hurzeler; Andrew Baillie; Glenys Dore; Nghi Phung; Paul S. Haber; Paul S. Haber (Frontiers Media S.A., 2022)
Background and AimsRecent studies indicate that sex may moderate the response to baclofen in the treatment of alcohol use disorder (AUD). We conducted a secondary analysis of a double-blind randomized controlled trial, Baclofen in the treatment of Alcohol Liver Disease (BacALD), to examine the moderating role of sex on treatment response to baclofen in reducing alcohol consumption.MethodsAlcohol-dependent patients (n = 104 including 74 men and 30 women) were treated for 12 weeks with baclofen (30 mg/day or 75 mg) or placebo. Predefined primary outcomes included time to lapse (any drinking) and relapse (≥ 5 drinks per day in men and ≥ 4drinks per day in women). Other outcomes included drinks per drinking day, the number of heavy drinking days, and percentage of days abstinent. We also examined the frequency of adverse events with an exploratory dose-response analysis.ResultsThere was a main effect of baclofen for days to first lapse for women (Log Rank: χ2 = 6.23, p = 0.01, d = 0.49) but not for men (Log Rank: χ2 = 2.48, p = 0.12, d = 0.22) and a marginal effect of baclofen for days to first relapse for women (Log Rank: χ2 = 3.15, p = 0.08, d = 0.27) but not for men (Log Rank: χ2 = 2.03, p = 0.16, d = 0.17). There were no significant effects of sex on the frequency of adverse events reported for the combined-dose or between-dose analysis (all p > 0.44).ConclusionBaclofen significantly delayed the time to lapse for women but not male participants. These findings provide some support for the hypothesis that sex may be a potential moderator of baclofen response in the treatment of AUD.Trial Registrationhttps://clinicaltrials.gov/ct2/show/NCT01711125, identifier: NCT01711125.